Social Media's Impact on Rape Myth Acceptance and Negative Affect in College Women: Examining the #MeToo and #HimToo Movement - Nomamiukor, Faith O. (Violence against women, 2024)
This study examined how the #MeToo movement, and backlash against it (#HimToo), influence rape myth acceptance (RMA) and negative affect among female sexual trauma survivors and controls. We randomly assigned college women (N = 389) to three social media conditions that either promoted RMA (#HimToo), challenged RMA (#MeToo), or did not address rape myths (general social media (GSM)). The findings demonstrated that women in the #HimToo condition reported more RMA, whereas women in the #MeToo and GSM conditions reported less negative affect. The results highlight that the way we talk about rape on social media influences momentary affect and RMA.